Autophagy in mammalian systems. - Klionsky, Daniel J. (Methods in enzymology ;, 2009)
Particularly in times of stress, like starvation and disease, higher organisms have an internal mechanism in their cells for chewing up and recycling parts of themselves. The process of internal "house-cleaning" in the cell is called autophagy - literally self-eating. Breakthroughs in understanding the molecular basis of autophagy came after the cloning of ATG1 in yeast. These ATG genes in yeast were the stepping stones to the explosion of research into the molecular analysis of autophagy in higher eukaryotes. In the future, this research will help to design clinical approaches that can turn on autophagy and halt tumor growth. In this volume, a robust slate of methods for conducting research are presented, establishing a consensus of appropriate criteria for monitoring autophagy. Along with Autophagy: Lower Eukaryotes, this volume marks the seminal collection of methods in the burgeoning field of autophagy